A relação gestão escolar e trabalho docente: estudo de caso numa escola municipal de Votorantim/SP. - Araújo, Tiago Antônio de (Universidade Federal de São Carlos, 2014)
In this work we present a qualitative study conducted in a municipal elementary school located in the city of Votorantim (SP). Informants participated in the survey as the team manager (director and education coordinator) and four teachers who teach in the early grades of elementary school. The main objectives of the research were: to determine whether the educational activities of the management team interfere in teaching developed in the studied school, see how the management team has been trying to implement improvements in the educational processes, and also the principles of a democratic management are used by the management team on ways to manage and organize the school. As an instrument of data collection, semistructured interviews, participant observation of the context of the subject and document analysis of school records were made. The data obtained in the investigative process were organized into categories for analysis, according to the research questions previously developed. As a result, it is concluded that the school management team seeks to engage democratically with the community, teachers, staff and students, so that its action seeks to collaborate with the teaching work, given the participatory work with teachers, in which subjects and anxieties brought on the context of the classroom are discussed and referrals are collectively determined.
Keywords: Gestão democrática; Organização escolar e trabalho docente; Escolas organização e administração Votorantim (SP); Democratização da educação; Prática de ensino; Democratic management; School organization and teaching; CIENCIAS HUMANAS::EDUCACAO::ADMINISTRACAO EDUCACIONAL